Membincang “Harry Potter”, Membaca Mitos - Sobur, Alex (FIkom Unisba, 2007)
In spite of the celebration of Harry Potter, JK Rowling as the author was accused as teaching and disseminating occultism among her readers. It is said that Harry Potter could turn children to become demons. This accusation raised concerns among parents and educators, especially Christians. Furthermore, a priest from New Mexico, Jack Brock, was threatening to burn Harry Potter volumes. Responding to the threat, JK Rowling was reported calm. Harry Potter still wins the heart of thousands children all over the world. A semiotic analysis toward Harry Potter books concludes that reality and imagination were created (not depicted, or mirrored) in the world of wizardry. Furthermore, an ideological analysis has successfully disclosed some imperialism signs being downplayed in the story plot.